2001
DOI: 10.1086/322639
|View full text |Cite
|
Sign up to set email alerts
|

Mass Vaccination of Children with Pertussis Toxoid—Decreased Incidence in Both Vaccinated and Nonvaccinated Persons

Abstract: During 1979-1995, there was no vaccination against pertussis in Sweden. With the aim of studying the epidemiology and transmission of pertussis, mass vaccination with pertussis toxoid of children born during the 1990s was instituted in the Göteborg area (population, 778,597) in 1995. Infants were offered 3 doses of pertussis toxoid combined with diphtheria and tetanus toxoids. Children aged > or =1 year were offered 3 doses of pertussis toxoid alone. From June 1995 through February 1999, 167,810 doses of pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…44 In February 1999, 55% of the children had received 3 injections of DTPTox. During the mass vaccination, B pertussis isolates decreased from 1200 to 64/year (P Ͻ .0001) and hospitalizations attributable to pertussis from 62 to 4/year (P Ͻ .0001).…”
Section: Mass Vaccination With Ptoxmentioning
confidence: 99%
See 1 more Smart Citation
“…44 In February 1999, 55% of the children had received 3 injections of DTPTox. During the mass vaccination, B pertussis isolates decreased from 1200 to 64/year (P Ͻ .0001) and hospitalizations attributable to pertussis from 62 to 4/year (P Ͻ .0001).…”
Section: Mass Vaccination With Ptoxmentioning
confidence: 99%
“…58 There was also a decrease in the isolation rate of B parapertussis during this period. 44 This could be attributable to the finding that B parapertussis is frequently found concurrently with B pertussis during outbreaks. 59 -61 Experiments in mice indicate that respiratory infection with B pertussis facilitates and prolongs colonization with B parapertussis.…”
Section: Multicomponent Acellular Vaccinesmentioning
confidence: 99%
“…Addition of inactivated PTx in the pertussis vaccine preparations has helped improve the vaccine's efficacy, suggesting that anti-PTx antibodies are important for protection against B. pertussis disease (15,33). Furthermore, a serological study indicated a positive correlation between anti-PTx antibody levels and protection from disease (34).…”
Section: Introductionmentioning
confidence: 99%
“…Pertussis virtually disappeared in the industrialized world during the 1970s and 1980s, and herd immunity was initially observed [25]. Clearly, pertussis vaccination prevents severe illness and reduces infection-and transmission rates but not to the same extent as seen for other vaccine preventable childhood diseases [26,27].…”
Section: Resurgence Of Pertussismentioning
confidence: 99%